Case report: Sigmoid strangulation from evisceration through a perforated rectal prolapse ulcer – An unusual complication of rectal prolapse. (2015) - Li, Jennifer Z.; Kittmer, Tiffaney; Forbes, Shawn; Ruo, Leyo
Highlights: Rectal prolapse occurs particularly in elderly females. Complications include incarceration, strangulation, and, rarely, perforation with evisceration of other viscera requiring urgent operation. Such complications can be prevented by a strict bowel regimen and avoidance of activities that increase intra-abdominal pressure. Prompt surgical consult is warranted if any signs or symptoms suggestive of complications from prolapse are present. Abstract: Introduction: Rectal prolapse occurs particularly in elder females and presentation can sometimes lead to complications such as strangulation and evisceration of other organs through the necrotic mucosa. Presentation of case: This is a case of a 61 year-old female with rectal prolapse complicated by rectal perforation through which a segment of sigmoid colon eviscerated and became strangulated. This patient initially presented with sepsis requiring ICU admission, but fully recovered following a Hartmann's procedure with a sacral rectopexy. Discussion: Complications of rectal prolapse include incarceration, strangulation, and rarely, perforation with evisceration of other viscera requiring urgent operation. This report provides a brief overview of complications associated with rectal prolapse, reviews similar cases of transrectal evisceration, and discusses the management of chronic rectal prolapse. Conclusion: Prompt surgical consult is warranted if any signs or symptoms suggestive of complications from prolapse are present.